Profile of Student's Self-Acceptance and Their Habits of Minds - Widodo, Suprih; Sari, Dian Permata; Hikmawan, Rizki; Majid, Nuur Wachid Abdul (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The freshman is an individual who is adapting to a new environment in college. This adaptation process differs from one another because each individual is unique and is influenced by many factors. The slow or fast process of adaptation will result in student achievement. Self-acceptance is an individual's ability to be able to accept the existence of oneself. While habits of minds is the ability of students to control positive behaviour in order to have confidence and have a steady personality. The study will use a qualitative and quantitative approach that seeks to uncover self-acceptance and habits of mind. Respondents in this study were first semester students at one university in Purwakarta who were selected by random sampling techniques. Data processing techniques will be carried out qualitatively and quantitatively. based on the results of the study there is a no positive relationship between self-acceptance and habits of mind of students, their self-acceptance is at a average size with good mathematical thinking habits